Clinical characteristics of liver transplant recipients with COVID-19 and analysis of risk factors for the severe disease - Sunya Fu; Dawei Chen; Yuqin Zhang; Mingjie Wu (Journal of Infection in Developing Countries)
Introduction: Liver transplant (LT) recipients were at a high risk of infection during the coronavirus disease 2019 (COVID-19) pandemic. Our purpose was to compare the clinical characteristics of severe and non-severe groups of LT recipients with COVID-19, and to analyze their risk factors for severe disease.